La estructura informativa en la enseñanza del español como lengua extranjera - Bánki, Timea (Verbum – Analecta Neolatina, 2018)
In free word order languages the word order is only apparently free, the information structure of the sentence strongly influences the succession of constituents. In these languages, there exists a kind of organizing principle which can be described and taught. Contemporary linguistics focuses on the information structure of different languages; however, we can find few traces of their results in second language acquisition and in textbooks. Classroom research also focuses on students’ knowledge of information structure and not on how this knowledge can be incorporated into foreign language studies. In my work I will try to answer the following questions: which fundamentals of information structure should be built into the teaching of Spanish as a second language in Hungary? To what extent do the results of a classroom experiment support the above questions?